Sn/SnO2@C composite nanofibers as advanced anode for lithium-ion batteries. (20th December 2015) - Hu, Yemin; Yang, Qiu-Ran; Ma, Jianmin; Chou, Shu-Lei; Zhu, Mingyuan; Li, Ying
Abstract: Sn/SnO2 @C composite nanofibers were successfully fabricated by a facile annealing strategy. The composite consists of an amorphous carbon matrix encapsulating carbon nanotubes decorated by ultrafine (<10 nm) SnO2 nanoparticles, with submicron Sn particles incorporated in the entangled networks of the composite nanofibers. When used as anode material for lithium ion batteries, the Sn/SnO2 @C composite nanofibers exhibited high initial charge capacity of 756 mAh g −1 at 100 mA g −1, excellent high-rate capacity of 190 mAh g −1 at 5 A g −1, and excellent capacity retention of 591 mAh g −1 after 100 cycles at 100 mA g −1 . High-resolution transmission electron microscopy, energy dispersive spectroscopy mapping, X-ray photoelectron spectroscopy, and electrochemical impedance spectroscopy were applied to investigate the origins of the excellent electrochemical Li + storage properties of Sn/SnO2 @C. It could be deduced that the ductile carbon matrix and free spaces in the composite nanofiber networks can effectively accommodate the strain of volume change during cycling, prevent the aggregation and pulverization of Sn/SnO2 particles, keep the whole structure stable, and facilitate electron and ion transport through the electrode.